Digital Editing of Early Modern English Handwritten Texts: Handling Scribal Errors and Corrections - Esteban-Segura, María Laura (My University, 2017)
An important philological question is how to edit texts. An edition always entails interpretation of the text and also of the socio-cultural context in which the manuscript was created and used. In new philological theory, and contrary to more traditional approaches, the individual manuscript versions, i.e., the textual witnesses, are regarded as valuable in their own right, as every textual witness tells us something about the culture of manuscripts (Carlquist 2004: 112). This is the approach followed for the digital editing of Early Modern English scientific writing in The Malaga Corpus of Early Modern English Scientific Prose. In this paper, we discuss the challenges that producing such type of edition pose. We will particularly focus on the issue of scribal errors and corrections and how the editor can treat and capture them in the edition. The texts included in the above-mentioned corpus will be analyzed for the purpose. The corpus includes manuscripts from the Hunterian Collection (Glasgow University Library), the Wellcome Collection (London Wellcome Library) and the Rylands Collection (University of Manchester Library). With regard to text types, these manuscripts hold specialized texts, surgical and anatomical treatises, as well as recipe collections and materia medica. References Calle-Martín, Javier et al. 2017. The Malaga Corpus of Early Modern English Scientific Prose (MCEMESP). Málaga: University of Málaga. Available from http:// modernmss.uma.es/. Carlquist, Jonas. 2004. Medieval Manuscripts, Hypertext and Reading. Visions of Digital Editions. Literary and Linguistic Computing 19/1: 105-118.
Keywords: Edición electrónica; Inglés moderno; MS Wellcome 213; Early Modern English; Digital editing